Порядок признания расходов от реализации винодельческой продукции в соответствии с национальными положениями бухгалтерского учета - Сурнина, Е.С. (Культура народов Причерноморья, 2004)
The article is dedicated to problems of correct forming of industry expenses. Unsettled legislative questions concerning the determination of the idea of enter property complexes and the reflection of the worn out rented property in the expenses of enterprises are considered.